Notes on some enigmatic taxa of limnoterrestrial rhabdocoels, with the description of two new species - Houben, Albrecht M.; Schwank, Peter; Proesmans, Willem; Bert, Wim; Artois, Tom J. (Zootaxa, 2015)
Six taxa of limnoterrestrial rhabdocoels are discussed, two of them, both belonging to Typhloplanidae Graff, 1905, are new to science. Adenoplea reisingeri n. sp. can be distinguished from its congeners by the absence of a separate seminal receptacle, the presence of a copulatory bursa and the fact that it has an unarmed copulatory organ. Carcharodopharynx schlitzensis n. sp. can be distinguished from C. arcanus (Reisinger, 1924) Poche, 1926, the only other species within the genus, by the fact that the cirrus bears spines. For four other taxa: Adenoplea perigraptopera Reisinger, 1924, A. meridionalis Kolasa, 1981, C. arcanus (Reisinger, 1924) Poche, 1926 and Archivortex silvestris Reisinger, 1924, new data on morphology and distribution are provided. Neotypes are designated for A. perigraptopera and C. arcanus.